ANALISIS PENGGUNAAN TEKNIK RESIPROCAL TERHADAP KEMAMPUAN MENELAAH UNSUR TEKS PUISI OLEH SISWA KELAS VII SMP - AMRON ZARKASIH RITONGA (LP2MTBM MAKARIOZ, 2021)
In poetry there are three things that must be considered apart from the physical element and the inner element, amongothers (1) identifying the content, namely determining the content of the poem read, what the poet said when writing thepoem. (2) The use of language, which is the language used by poets in writing poetry. The language used in writing poetry isa concise language, but rich in meaning. (3) Words (connotations and denotations), i.e. connotations are meanings thatundergo changes in meaning while denotation is meaning that does not change. The meaning of denotation is also calledstraightforward meaning. The word does not have any meaning. The meaning is in accordance with the original concept, asit is. To find out the Resiprocal Analysis of students' ability to study the elements of poetry text building, use standard scores.Should pay more attention to the development of learning techniques used in schools, especially in learning to study theelements of poetry text building. Poetry has elements that build poetry texts that support the beauty of a poem. The elementsof this poem's building text consist of two parts, namely, the inner element and the physical element. The inner element isdivided into (a) the theme, (b) the tone, (c) the sense, (d) the mandate. While in the physical element is divided into (a)diction, (b) arimajian, (c) figurative language, (d) the word concret, (e) typography (facial layout), (f) rhythm (rhythm), (g)rhyme.